(untitled) (Journal of University of Babylon for Engineering Sciences, 2022)
Power electronics converters play a major role in various energy processing applications. In many instances the need arises to use two converters to achieve power processing, conditioning or both. In this work, two converter systems are studied, which is based on two multiphase/multilevel converters. The main objective is to process AC power from a source which can be a distributed energy source (DER) by converting it to DC before injecting it into another AC system. An 18 pulse multiphase rectifier is used for the first objective. The second processing task, which involves converting the DC power back to AC is achieved by five level neutral point clamped converter (NPC). Results verify the benefits of the multiphase rectifier in producing a smooth DC voltage. On the other side, the five level NPC revels an interesting feature of high fundamental voltage.